The Effect of The Number Of Members, Own Capital, External Capital, and Business Volume on The Remaining Operating Results (Shu) In Cooperatives In Central Kalimantan Province Year 2016-2019 - Muhammad Daffa Putra; Sumarsono, Hadi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2023)
The role of cooperatives is very useful in improving the regional economy and community welfare. This study aims to determine the influence given by the number of members, external capital, own capital, and business volume, both partially and simultaneously on the Remaining Operating Results (SHU) of Cooperatives in Central Kalimantan Province in 2016-2019. The object used is a cooperative located in Central Kalimantan Province. The data used are secondary data in the form of data on the number of members, external capital data, own capital data, business volume data, and SHU data in the 2016-2019 period. The data were analyzed using multiple linear regression, Chow test, Hausman test, partial test, simultaneous test, and coefficient of determination. The results explain that the variable number of members has a positive relationship, but does not have a significant effect on SHU. Meanwhile, the variables of external capital, own capital, and business volume have a positive relationship and have a significant influence on SHU.